Mice with either diminished or elevated levels of anti-Müllerian hormone have decreased litter sizes†. Issue 1 (21st November 2017) - McLennan, Ian S; Koishi, Kyoko; Batchelor, Nicola J; Pankhurst, Michael W
Abstract: Anti-Müllerian hormone (AMH) is both a gonadal hormone and a putative paracrine regulator of neurons, the uterus, and the placenta. A mouse line with neuronal expression of AMH ( Thy1.2-AMH ) was generated to examine the role of paracrine AMH in the brain. The mice had normal behavior, but unexpectantly AMH was present in the circulation of the transgenic mice. Thy1.2-AMH Tg/0 studs sired pups with a normal frequency, when mated with wild-type dams. In stark contrast, Thy1.2-AMH Tg/0 dams rarely gave birth, with evidence of spontaneous midgestational abortion. This leads to the hypothesis that AMH influences the capacity of dams to carry concepti to term. This hypothesis was tested by mating AMH-deficient ( Amh −/− ), Thy1.2-AMH Tg/0, and wild-type dams when 49-, 80-, and 111 days old, using proven wild-type studs. The litter sizes from the first two matings and the number of fetuses present on the 10th day of gestation of the third mating were recorded. Thy1.2-AMH Tg/0 dams carried near normal numbers of midterm fetuses, but typically produced no pups, indicating that extensive late resorption of fetuses was occurring. Amh −/− dams exhibited a lesser reduction in litter size than the Thy1.2-AMH Tg/0 dams, with no evidence of enhanced loss of fetuses. In conclusion, this study provides the first evidence that high AMH levels can cause a miscarriage phenotype and that the absence of AMH affects reproductive output. Summary Sentence: Prevention of the pregnancy-related decline in circulating anti-Müllerian hormone levels leads to midterm abortion.